The Effects of Ovine Whey Powders on Durum Wheat-Based Doughs - Nicola Secchi; Costantino Fadda; Massimo Piccinini; Ivo Pinna; Antonio Piga; Pasquale Catzeddu; Simonetta Fois (Journal of Food Quality)
Two types of ovine whey powder, with different protein content, were added at increasing substitution rates to two types of semolina, one with strong and tenacious gluten and the other with weak and sticky gluten. For each dough the optimum mixing time and hydration level were calculated using the consistograph. The whey powder negatively affected the leavening volume of all doughs, at all percentages except the lowest one (5%), mainly because of its effects on the elastic component of gluten as measured with a stress relaxation test. Differences of the secondary structure of gluten proteins among samples were investigated by analyzing the amide I band in the Fourier transform infrared spectra of the dough. Weak and strong semolina showed a different relative percentage of α-helix, random coil, and β-sheet structures. The longer mixing times for dough formation when using semolina with strong gluten led to an increase in α-helices and random coils, which caused a worse leavening performance than the weak-gluten semolina.